2022
DOI: 10.4049/jimmunol.2200198
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Lung Infection Impairs Host Immunity against Secondary Bacterial Infection by Promoting Lysosomal Dysfunction

Abstract: Postviral bacterial infections are a major health care challenge in coronavirus infections, including COVID-19; however, the coronavirus-specific mechanisms of increased host susceptibility to secondary infections remain unknown. In humans, coronaviruses, including SARS-CoV-2, infect lung immune cells, including alveolar macrophages, a phenotype poorly replicated in mouse models of SARS-CoV-2. To overcome this, we used a mouse model of native murine β-coronavirus that infects both immune and structural cells t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…ROS-independent conidial clearance in both macrophages and neutrophils requires phagolysosome maturation to create an acidic environment, which is necessary for conidial killing ( 51 , 52 ). A recent study also showed that betacoronavirus infection can lead to lysosome destruction, affect its acidification, and reduce bacterial clearance in the macrophage ( 53 ). To assess phagolysosome maturation in the neutrophils and monocytes within the IAV- Af -superinfected lungs, we used pHrodo-zymosan staining.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS-independent conidial clearance in both macrophages and neutrophils requires phagolysosome maturation to create an acidic environment, which is necessary for conidial killing ( 51 , 52 ). A recent study also showed that betacoronavirus infection can lead to lysosome destruction, affect its acidification, and reduce bacterial clearance in the macrophage ( 53 ). To assess phagolysosome maturation in the neutrophils and monocytes within the IAV- Af -superinfected lungs, we used pHrodo-zymosan staining.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the upstream signal that may drive defective fungal clearance in the IAV- Af superinfection mice in our model, we examined antifungal gene expression in isolated immune cells. Based on viral-bacterial superinfection literature, we expected to observe an anti-inflammatory gene expression profile after IAV infection and during early fungal infection ( 53 56 ). However, we observed that immune cells from IAV- Af superinfection mice displayed increased inflammatory gene transcript levels and decreased anti-inflammatory cytokine gene transcript levels ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ROS-independent conidial clearance in both macrophages and neutrophils requires phagolysosome maturation to create an acidic environment which is necessary for conidial killing (56, 57). A recent study also showed that β-coronavirus infection can lead to lysosome destruction, affect its acidification, and reduce bacterial clearance in macrophage (58). To assess phagolysosome maturation in the neutrophils and monocytes within the IAV- Af superinfected lungs, we used pHrodo-Zymosan staining.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the upstream signal that drives defective fungal clearance in the IAV- Af superinfection mice in our model, we examined antifungal gene expression in isolated immune cells. Based on viral-bacterial superinfection literature, we expected to observe an antiinflammatory expression profile after IAV infection and during early fungal infection (5861). However, we observed that immune cells from IAV- Af superinfection mice displayed increased inflammatory gene transcript levels and decreased anti-inflammatory cytokine gene transcript levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa strain PA01 was grown in tryptic soy broth (TSB; BD Biosciences, catalog no. 211825) at 37°C overnight as shown in our publication (Peng et al , 2022 ), and Streptococcus pneumoniae strain TIGER4 was purchased from ATCC and grown in a humidified incubator with 5% CO 2 in Todd Hewitt broth (THB; BD Biosciences, catalog no. 249240).…”
Section: Methodsmentioning
confidence: 99%